Design, comparison and optimisation of permanent magnet flux switching motor (PMFSM) with various slot pole configuration - Mohamed, Abdullahi Abdi (2021)
This project report is about comparison between conventional permanent magnet flux switching machine (PMFSM) with double stator flux switching machine (DS-PMFSM). Due to the unique design of double stator single rotor motor itself, many research has been developed but not being compare to different kind of motor. The purpose of this study is to observe the capability of each different motor. The test will be also conducted in no load and load situations. Result each of the motor will be compare. JMAG design 16 is being use as a platform to develop both motor. Although both machine is silent pole type motor, each of them have a different topology and characteristic. By using JMAG, each of the motor is been constructed, starting from JMAG sketch that are used to sketch the motor topology. The both motor topology need to be almost the same with different in stator design. After that, by using JMAG designer, both electrical motor material, condition circuit, mesh value and properties have to be exactly the same as dimmed variable. Thus an in depth study is about the performance of both motor is conducted. Result shows that under no load condition the DS-PMFSM has a lower cogging torque then conventional PMFSM. Beside that went compare with flux line, flux density and induce EMF conventional PMFSM have advantage over DS-PMFSM. Went both motor is test with load test, it is show a large performance gap. Load test shown that conventional PMFSM has a higher torque, power and speed went compare. Result conclude that conventional PMFSM has a better performance in all the load test and in flux line, flux density, induce EMF for no load. However, DS-PMFSM has an advantage in cogging torque with lower cogging and reduce noise. Although the 12S/14P motor is selected for securing the initial highest torque of 11.5 Nm and achieved the target average torque/power after using parameter optimisation method (POM).